2006
DOI: 10.1007/s10265-006-0052-1
|View full text |Cite
|
Sign up to set email alerts
|

Annual growth of invasive Larix kaempferi seedlings with reference to microhabitat and ectomycorrhizal colonization on a volcano

Abstract: To investigate the seedling growth of a biologically-invasive larch Larix kaempferi (Lamb.) Carr. on Mount Koma, Japan, seedlings were excavated from three microhabitats (bareground = BA, Salix reinii patch = SP, and Larix understory = LU) in three elevational zones.Seedlings showed the highest ectomycorhhizal (ECM) colonization percentage in the most shaded microhabitat, LU. ECM colonization percentages in BA and SP were found to decrease with decreasing elevation. These results inferred that the ECM colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Komagatake (Sasaoka et al 1999;Qu et al 2004a;Tsuyuzaki 2005, 2009;Akasaka et al 2007). Yang et al (1998) suggested that the ECM types identified by morphology increased with increasing altitude up to 700 m a.s.l.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Komagatake (Sasaoka et al 1999;Qu et al 2004a;Tsuyuzaki 2005, 2009;Akasaka et al 2007). Yang et al (1998) suggested that the ECM types identified by morphology increased with increasing altitude up to 700 m a.s.l.…”
Section: Introductionmentioning
confidence: 95%
“…hereafter larch) forms symbiosis with ECM fungi (e.g., Yang et al 1998;Qu et al 2004b;Nara 2006;Akasaka et al 2007) and is distributed across subalpine areas of central Japan (Horikawa 1972). Larch is able to regenerate on slopes of volcanos (Ishikawa et al 1978;Maeda et al 1978;Tanaka et al 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such site-specific dissimilarities have been observed in the lava flow at Mt. OshimaKoma of Hokkaido island, Japan (Akasaka et al 2007;Kayama et al 2015). In a study of Japanese larch (Larix kaempferi) seedlings from three microhabitats in three elevation zones, the results showed that the highest ECM colonization rate occurred in the most shaded micro-habitat with Larix understory than in the other two habitats (bare-ground and Salix reinii patch).…”
Section: Ecm Colonization Rate and Species Diversity Under Elevated Comentioning
confidence: 79%
“…Age was evaluated for 90 L. kaempferi seedlings, confirming that they were ≤ 10 year old (Akasaka et al 2007). Small saplings of Betula and Populus were not always identified to species at the first census.…”
Section: Plot Surveymentioning
confidence: 99%